Ethical Branding and Consumer Trust in Emerging Markets: A Comparative Systematic Review of Local and Global Brands in Indonesia - Rosari, Dina (TechTalent & Business Review, 2025)
This study aims to systematically examine how ethical branding measured through Corporate Social Responsibility (CSR), green marketing, brand transparency, and digital engagement affects consumer trust in the Indonesian market, using a Systematic Literature Review (SLR) approach, 51 peer-reviewed journal articles published between 2020 - 2025 were analyzed, the review reveals that all four variables positively influence consumer trust, albeit to varying degrees, CSR rooted in local values significantly fosters emotional connection and social legitimacy, green marketing is effective only when coupled with transparency and verifiable action, helping to avoid greenwashing skepticism, brand transparency emerges as a foundational element for brand credibility, particularly among critical digital consumers, digital engagement enhances trust by facilitating two-way ethical communication and community interaction. The study also finds that local brands leverage culture-based trust and community narratives, while global brands emphasize international certifications and reputational consistency. From a theoretical perspective, the findings contribute to the contextualization of attachment theory in branding by showing how emotional bonds to ethically aligned brands drive long-term trust and loyalty. This research proposes a contextual ethical branding model for emerging markets, integrating localized CSR, transparent green communication, and trust-based digital interaction. The model highlights the importance of aligning universal ethics with cultural relevance and digital strategies in building sustainable consumer trust.